Diagnostic indicators and lifestyle interventions of metabolic-associated fatty liver disease - Chen, Tianzhu; Qin, Xiang; Jiang, Jianping; He, Beihui (Frontiers in Nutrition, 2024)
MAFLD has become a major global health problem and is the leading cause of liver disease worldwide. The disease progresses from a simple fatty liver to gradual fibrosis, which progresses to cirrhosis and even hepatocellular liver cancer. However, the methods currently used for diagnosis are invasive and do not facilitate clinical assessment of the condition. As a result, research on markers for the diagnosis of MAFLD is increasing. In addition, there are no clinical medications for the treatment of MAFLD, and lifestyle interventions remain effective in the prevention and treatment of MAFLD. In this review, we attempt to make a summary of the emerging diagnostic indicators and effective lifestyle interventions for MAFLD and to provide new insights into the diagnosis and treatment of MAFLD.